Respuestas
Respuesta dada por:
2
ecuación ....1
![\frac{x}{6} + \frac{y}{3} - \frac{z}{4} = 1 \frac{x}{6} + \frac{y}{3} - \frac{z}{4} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B6%7D+%2B+%5Cfrac%7By%7D%7B3%7D+-+%5Cfrac%7Bz%7D%7B4%7D+%3D+1)
![\frac{2x + 4y - 3z}{12} = 1 \frac{2x + 4y - 3z}{12} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B2x+%2B+4y+-+3z%7D%7B12%7D+%3D+1)
2x + 4y - 3z = 12....ec 1
ecuación .....2
![\frac{x}{3} + \frac{y}{4} + \frac{z}{2} = - 3 \frac{x}{3} + \frac{y}{4} + \frac{z}{2} = - 3](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B3%7D+%2B+%5Cfrac%7By%7D%7B4%7D+%2B+%5Cfrac%7Bz%7D%7B2%7D+%3D+-+3)
![\frac{4x + 3y + 6z}{12} = - 3 \frac{4x + 3y + 6z}{12} = - 3](https://tex.z-dn.net/?f=+%5Cfrac%7B4x+%2B+3y+%2B+6z%7D%7B12%7D+%3D+-+3+)
4x + 3y + 6z = -36........ec 2
ecuación ....3
![\frac{x}{2} + \frac{y}{2} - \frac{z}{ 3} = 7 \frac{x}{2} + \frac{y}{2} - \frac{z}{ 3} = 7](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B2%7D+%2B+%5Cfrac%7By%7D%7B2%7D+-+%5Cfrac%7Bz%7D%7B+3%7D+%3D+7)
![\frac{3x + 3y - 2z}{6} = 7 \frac{3x + 3y - 2z}{6} = 7](https://tex.z-dn.net/?f=+%5Cfrac%7B3x+%2B+3y+-+2z%7D%7B6%7D+%3D+7)
3x + 3y - 2z = 42......ec3
operación :
2x + 4y - 3z = 12....ec 1
4x + 3y + 6z = -36...ec 2
-------------------------
(2) 2x+4y-3z =12
4x + 3y + 6z = -36
--------------------------
4x + 8y - 6z = 12
4x + 3y + 6y = -36
--------------------------
8x + 11y = -24 ....ec4
4x + 3y + 6z = -36...ec 2
3x + 3y - 2z = 42......ec3
---------------------------
4x + 3y + 6z = -36
(3)3x + 3y - 2z = 42
---------------------------
4x + 3y + 6z = -36
9x + 9y - 6z = 126
---------------------------
13x + 12y = 90.....ec4
hallamos "x"
8x + 11y = -24 ....ec4
13x + 12y = 90.....ec4
-----------------------
(12) 8x+11y = -24
(-11) 13x + 12y = 90
-----------------------
96x + 132y = -288
143x - 132y =- 990
-----------------------
239x = - 1278
x = -1278/239
x = 5,34
2x + 4y - 3z = 12....ec 1
ecuación .....2
4x + 3y + 6z = -36........ec 2
ecuación ....3
3x + 3y - 2z = 42......ec3
operación :
2x + 4y - 3z = 12....ec 1
4x + 3y + 6z = -36...ec 2
-------------------------
(2) 2x+4y-3z =12
4x + 3y + 6z = -36
--------------------------
4x + 8y - 6z = 12
4x + 3y + 6y = -36
--------------------------
8x + 11y = -24 ....ec4
4x + 3y + 6z = -36...ec 2
3x + 3y - 2z = 42......ec3
---------------------------
4x + 3y + 6z = -36
(3)3x + 3y - 2z = 42
---------------------------
4x + 3y + 6z = -36
9x + 9y - 6z = 126
---------------------------
13x + 12y = 90.....ec4
hallamos "x"
8x + 11y = -24 ....ec4
13x + 12y = 90.....ec4
-----------------------
(12) 8x+11y = -24
(-11) 13x + 12y = 90
-----------------------
96x + 132y = -288
143x - 132y =- 990
-----------------------
239x = - 1278
x = -1278/239
x = 5,34
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años